Effectiveness and Acceptance of a Smartphone-Based Virtual Agent Screening for Alcohol and Tobacco Problems and Associated Risk Factors During COVID-19 Pandemic in the General Population - Auriacombe, Marc; Fournet, Lucie; Dupuy, Lucile; Micoulaud-Franchi, Jean-Arthur; de Sevin, Etienne; Moriceau, Sarah; Baillet, Emmanuelle; Alexandre, Jean-Marc; Serre, Fuschia; Philip, Pierre (Frontiers in Psychiatry, 2021)
Background: During the current COVID-19 pandemic, alcohol and tobacco are the most available substances for managing stress and can induce a risk of addiction. KANOPEE is a smartphone application available to the general population using an embodied conversational agent to screen for experience of problem with alcohol/tobacco use, and provide follow-up tools for brief intervention. Objectives: To determine if the smartphone KANOPEE application could identify people at risk for alcohol and/or tobacco use disorders in the context of the current COVID-19 epidemic; to assess adherence to a 7-day follow-up use diary and to evaluate trust and acceptance of the application. Methods: The conversational agent, named Jeanne, interviewed participants about perceived problems with use of alcohol and tobacco since pandemic, explored risk for tobacco and alcohol use disorder with the CDS-5 and CAGE and experience of craving for each substance. Descriptive, univariate and multivariate analyses were performed to specify personalized associations with reporting a problem with alcohol/tobacco use, descriptive analysis reported experience with the intervention and acceptance and trust in the app. Results: From April 22 to October 26, 2020; 1588 French participants completed the KANOPEE interview and 318 answered the acceptance and trust scales. 42% of tobacco users and 27% of alcohol users reported problem use since the pandemic. Positive screening with CDS-5 and CAGE, and craving were associated with reported problem use (p<.0001). Lockdown period influenced alcohol (p<.0005) but not tobacco use (p>.05). 88% users reported KANOPEE was easy to use and 82% found Jeanne to be trustworthy and credible. Conclusion: KANOPEE was able to screen for risk factors for Substance Use Disorder and was acceptable to users. Reporting craving and being at risk for substance use disorder seem to be early markers to be identified. Alcohol problem use seems to be more reliant on contextual conditions as confinement. This method is able to offer acceptable, brief and early intervention with minimal delay for vulnerable people.